Antidotal effect of cyclosporine A against α-amanitin toxicity in CD-1 mice, at clinical relevant doses. (August 2022) - Garcia, Juliana; Carvalho, Alexandra; das Neves, Ricardo Pires; Malheiro, Rui; Rodrigues, Daniela F.; Figueiredo, Pedro R.; Bovolini, Antonio; Duarte, José Alberto; Costa, Vera Marisa; Carvalho, Félix
Abstract: Amanita phalloides is one of the most toxic mushrooms worldwide, being responsible for the majority of human fatal cases of mushroom intoxications. α-Amanitin, the most deleterious toxin of A. phalloides, inhibits RNA polymerase II (RNAP II), causing hepatic and renal failure. Herein, we used cyclosporine A after it showed potential to displace RNAP II α-amanitin in silico . That potential was not confirmed either by the incorporation of ethynyl-UTP or by the monitoring of fluorescent RNAP II levels. Nevertheless, concomitant incubation of cyclosporine A with α-amanitin, for a short period, provided significant protection against its toxicity in differentiated HepaRG cells. In mice, the concomitant administration of α-amanitin [0.45 mg/kg intraperitoneal (i.p.)] with cyclosporine A (10 mg/kg i.p. plus 2 × 10 mg/kg cyclosporine A i.p. at 8 and 12 h post α-amanitin) resulted in the full survival of α-amanitin-intoxicated mice, up to 30 days after the toxin's administration. Since α-amanitin is a substrate of the organic-anion-transporting polypeptide 1B3 and cyclosporine A inhibits this transporter and is a potent anti-inflammatory agent, we hypothesize that these mechanisms are responsible for the protection observed. These results indicate a potential antidotal effect of cyclosporine A, and its safety profile advocates for its use at an early stage of α-amanitin intoxications. Highlights: Cyclosporine A has a potential to displace α-amanitin from RNAP II in silico. Cyclosporine A does not displace α-amanitin from RNAP II in vitro. Brief concomitant incubation of cyclosporine A with α-amanitin protects differentiated HepaRG cells. In mice, the concomitant use of cyclosporine A with α-amanitin leads to full survival.